Human-Computer Interaction Enhancement for Linux Cli Application using Telegram Bot Piping - Wicaksono, Herlambang; Azzahra, Fadel; Setiawan, Hermawan (KH. A. Wahab Hasbullah University, 2024)
This paper proposes an innovative method to enhance Human-Computer Interaction (HCI) for Linux Command Line Interface (CLI) applications by integrating Telegram bot piping. Despite the power of CLI, its complexity often deters users, particularly those less experienced with technology. We introduce a solution leveraging Telegram bots to provide a more intuitive and accessible interface for interacting with CLI tools. Users can issue commands via Telegram, receiving real-time feedback and executing tasks without extensive CLI knowledge. Our study includes design, implementation, and evaluation phases, demonstrating high user satisfaction with the Telegram bot integrated CLI applications. The approach significantly improves usability, reduces the learning curve, and broadens the accessibility of Linux systems. The user feedback indicated high satisfaction with the Telegram bot integrated CLI applications, with users finding it effective, user-friendly, and preferable over traditional CLI interfaces, with a user satisfaction score of 95.3%